2023
DOI: 10.2169/internalmedicine.0027-22
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Kampo Medicine Treatment for Mild-to-moderate COVID-19: A Multicenter, Retrospective, Observational Study by the Integrative Management in Japan for Epidemic Disease (IMJEDI Study-observation)

Abstract: Objective Patients in whom coronavirus disease 2019 was suspected or confirmed between January 1, 2020, and October 31, 2021, were enrolled from Japanese hospitals in this multicenter, retrospective, observational study. Methods Data on the treatment administered (including conventional and Kampo medicine) and changes in common cold-like symptoms (such as fever, cough, sputum, dyspnea, fatigue, and diarrhea) were collected from their medical records. The primary outcome was the number of days without a fever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A case series of mild and moderate COVID-19 patients treated with KT and SSKKS has already been reported ( Irie et al, 2021a ; 2021b ). We have reported that early Kampo medicine treatment including KT and SSKKS may suppress illness worsening risk in COVID-19 cases without steroid use in a multicenter, retrospective, observational study ( Takayama et al, 2022 ). The present study was conducted based on these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case series of mild and moderate COVID-19 patients treated with KT and SSKKS has already been reported ( Irie et al, 2021a ; 2021b ). We have reported that early Kampo medicine treatment including KT and SSKKS may suppress illness worsening risk in COVID-19 cases without steroid use in a multicenter, retrospective, observational study ( Takayama et al, 2022 ). The present study was conducted based on these results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combined use of KT and SSKKS can alleviate symptoms of the common cold, pharyngitis, bronchitis, and pneumonia, with multifunctional antiviral and anti-inflammatory effects ( Arita et al, 2020 ). In a multicenter, retrospective, observational study showed that early treatment with Kampo medicines including KT and SSKKS may suppress illness worsening risk in COVID-19 cases without steroid use ( Takayama et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have been conducted for patients with mild to moderate COVID-19 using RNA polymerase inhibitors, protease inhibitors, antiparasitic drugs, and kampo medicines in Japan (Takayama et al 2021;Clinical Practice Guidance Review Committee 2021c). The results from these trials are awaited.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed clinical studies into the acute stage of COVID-19. Confirmed and suspected COVID-19 patients were enrolled [4]. Treatments including conventional and Kampo medicine, as well as changes in symptoms were collected from their medical records.…”
mentioning
confidence: 99%
“…The study is ongoing in collaboration with JSOM and nine medical institutions. Takao Namiki 2 Toshiaki Makino 3 Ryutaro Arita 1 Hiroshi Odaguchi 4 Takashi Ito 5…”
mentioning
confidence: 99%